Acute Hemorrhagic Rectal Ulcer Syndrome: An Uncommon Cause of Exsanguinating Hematochezia - Jacob, Anu; Zacharia, George Sarin (International Journal of Human and Health Sciences (IJHHS), 2025)
Acute hemorrhagic rectal ulcer syndrome (AHRUS) is a seldom-seen source of substantial, painless rectal bleeding, typically found in elderly individuals who frequently have multiple concurrent health conditions. The precise underlying causes of this condition remain elusive, as do the most effective treatment approaches. This report presents a case involving an elderly male who experienced profuse rectal bleeding, was diagnosed with AHRUS, and successfully managed through endoscopic intervention. This case report underscores the challenges in diagnosing AHRUS and highlights the importance of considering this syndrome in elderly patients with painless, massive rectal bleeding after excluding other potential causes. International Journal of Human and Health Sciences Vol. 09 No. 02 Apr’25 Page: 131-133